2022
DOI: 10.1038/s41419-022-04813-w
|View full text |Cite
|
Sign up to set email alerts
|

Cancer cells adapt FAM134B/BiP mediated ER-phagy to survive hypoxic stress

Abstract: In the tumor microenvironment, cancer cells experience hypoxia resulting in the accumulation of misfolded/unfolded proteins largely in the endoplasmic reticulum (ER). Consequently, ER proteotoxicity elicits unfolded protein response (UPR) as an adaptive mechanism to resolve ER stress. In addition to canonical UPR, proteotoxicity also stimulates the selective, autophagy-dependent, removal of discrete ER domains loaded with misfolded proteins to further alleviate ER stress. These mechanisms can favor cancer cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…These data support the idea that ER-phagy acts as a stress response mechanism that works in concert with the UPR to resolve the stressful condition. Consistently, MCF-7 cells (breast cancer) survive hypoxia induced ER stress by promoting FAM134B mediated ER-phagy ( Chipurupalli et al, 2022 ).…”
Section: Er-phagymentioning
confidence: 96%
“…These data support the idea that ER-phagy acts as a stress response mechanism that works in concert with the UPR to resolve the stressful condition. Consistently, MCF-7 cells (breast cancer) survive hypoxia induced ER stress by promoting FAM134B mediated ER-phagy ( Chipurupalli et al, 2022 ).…”
Section: Er-phagymentioning
confidence: 96%
“…Interestingly, the small molecule vitexin, a plant-derived flavone O-glycoside, inhibits ER-phagy by disrupting the FAM134B-BIP complex, together with the ability of BIP to chaperone proteins ( Figure 3 ). This double effect of the inhibition of BIP’s folding capacity and of ER-phagy repression suppresses breast cancer growth ( 80 ). Thus, it has been suggested that targeting the FAM134-BIP complex may offer a valid strategy to treat cancer.…”
Section: Er-phagy and Cancermentioning
confidence: 99%
“…Apoptosis signal-regulated kinase (ASK1) is a downstream signaling molecule of TRAF2 that activates c-Jun N -terminal protein kinase, which is triggered to maintain ER homeostasis by autophagy [ 97 , 102 ]. Cancer cells survive by inducing p62-dependnt canonical autophagic degradation to overcome ER damage [ 103 ]. For example, ER stress inducers such as TM, brefeldin A, and thapsigargin (TG) activate autophagy in colon and prostate cancer cells, effectively protecting cells against ER stress-induced cell death [ 104 ].…”
Section: Canonical Pathway Regulates Er-stress Responsementioning
confidence: 99%
“…Nevertheless, the loss of ER-phagy receptor FAM123B increases ER stress and reduces cell proliferation in a breast cancer xenograft model [ 103 ]. Limited information on FAM134B necessitates further investigation to identify the precise protective mechanism.…”
Section: Er-specific Autophagymentioning
confidence: 99%
See 1 more Smart Citation